Encyclopaedia Britannica 2005 student encylopedia - Encyclopaedia Britannica Inc. (Chicago : Encyclopaedia Britannica, 2005)
Contains atlas with 1,750 cklickable map, Merriam - Webster's student dictionary and thesaurus and online learning games and interactive study online.
Keywords: Electronic encyclopedias; Encyclopedias and dictionaries